2015
DOI: 10.1097/jto.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Modified Masaoka Stage and Size Are Independent Prognostic Predictors in Thymoma and Modified Masaoka Stage Is Superior to Histopathologic Classifications

Abstract: Histopathologic classifications of thymomas are associated with prognosis but are in general not independent predictors of outcome. Modified Masaoka stage and proposed Moran staging are independent prognostic parameters for thymoma and superior to histopathologic classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
5
50
1
Order By: Relevance
“…Some studies did not find any significant differences in outcome between patients with encapsulated thymomas and patients with thymomas that invade into the thymic or perithymic adipose tissue. 33,42,43 In contrast, a recent study by Roden et al 40 showed significantly worse overall survival for patients with thymomas that invaded through the capsule versus encapsulated thymomas. This controversy might, at least in part, be due to interobserver variability.…”
Section: Evolution Of the Staging Classification Of Thymic Epithelialmentioning
confidence: 68%
See 1 more Smart Citation
“…Some studies did not find any significant differences in outcome between patients with encapsulated thymomas and patients with thymomas that invade into the thymic or perithymic adipose tissue. 33,42,43 In contrast, a recent study by Roden et al 40 showed significantly worse overall survival for patients with thymomas that invaded through the capsule versus encapsulated thymomas. This controversy might, at least in part, be due to interobserver variability.…”
Section: Evolution Of the Staging Classification Of Thymic Epithelialmentioning
confidence: 68%
“…Furthermore, there were no differences in outcome between stages IIa, b, and c. The authors considered, however, that distinction was still important because of possible differences in treatment. The prognostic significance of the proposed Moran staging for thymomas was later confirmed by Roden et al, 40 although in that study, patients with stage 0 disease had a significantly better overall survival than stage I patients.…”
Section: Evolution Of the Staging Classification Of Thymic Epithelialmentioning
confidence: 68%
“…In other reports, the median maximal diameter of usual thymomas was 57-68 mm, and our case series was 50 mm, which was smaller than usual thymomas. 10,12,13) However, these cases were greater than or equal to 40 mm. Pathologically, only one case had type AB, and the other eight had type B (Type B1:B2:B3 = 4:3:1 cases).…”
Section: Commentmentioning
confidence: 94%
“…Our all three cases were accompanied with MG, meanwhile remaining six of seven reported cases were not accompanied with MG. Their complication rate of MG with thymoma was between 20% and 40%, and the rate of MG with type B thymoma was 35%-49%. [10][11][12][13] Although the complication rate with MG could not simply compare due to the small number of cases, it was approximated rate. In other reports, the median maximal diameter of usual thymomas was 57-68 mm, and our case series was 50 mm, which was smaller than usual thymomas.…”
Section: Commentmentioning
confidence: 99%
“…Complete resection has been shown to be a favorable prognostic parameter for TET (1)(2)(3)(4). Resectability of these tumors usually depends on their size and stage with reported rates of complete resection ranging between 100% for Masaoka stage I and 0-78% for stage IV tumors (1,3).…”
mentioning
confidence: 99%